Optimization of a Two-Step Centrifugation Protocol for Bovine Platelet-Rich Plasma - Kim Mu-Young; Han Hyun-Jung (Acta Veterinaria, 2022)
Platelet-rich plasma ( PRP), an autologous platelet concentrated in plasma, is a source of diverse growth factors and is extensively utilized to promote tissue healing. Most of the clinical and laboratory investigations in veterinary medicine have focused on horses and dogs. Consequently, the types and detailed conditions of the PRP preparation method are based on those species. However, in bovine medicine, only a few studies have investigated the species-specific characteristics of bovine platelets. The aim of this study was to optimize the conditions of a two-step centrifugation method for bovine PRP. Whole blood samples were obtained from eight healthy lactating Holstein-Friesian cows. Eight running conditions for the first and second centrifugations each were evaluated based on the platelet recovery rate, the concentration of growth factors, and the adenosine diphosphate (ADP)-induced aggregation response, which reflects the premature platelet activation caused by the centrifugation process. The results of this study showed that for the first and second centrifugations, 900×g for 10 minutes and 1250×g for 15 minutes, respectively, were the most suitable conditions for the platelet recovery rate, and the concentration of growth factors was highest under these conditions without significant activation of premature platelet aggregation. Thus, we established an optimal two-step centrifugation protocol for bovine PRP that should provide a better understanding of bovine platelets.